Legitimacy of Coastal Resource Management Through Environmental Accounting of Blue Carbon Assessment of Mangrove Forests in Surumana Village - Retno Wulandari; Mustamin Mustamin; Betty Betty; Jamaluddin Jamaluddin (UNIVED Press, 2026)
Environmental accounting is needed to explain the interaction between the economy and the environment, while carbon estimation is a form of reporting the value of carbon or biomass produced from mangrove forests for sustainable coastal resource management in Surumana Village, South Banawa District. This study aims to calculate the amount of biomass and, as a form of legitimacy for interested parties, report the biomass produced by mangrove forests for coastal resource management. A mixed-methods approach is the method used in this study through interviews, observations, and plot sampling as data collection techniques. The results show that the carbon absorption of the mangrove ecosystem in Surumana Village is 153,97 tCO2e with an asset value of Rp 22.171.680. This monetary value provides an absolute legal mandate for the Regional Government (Environmental Agency) to actively participate and implement Presidential Decree No. 98/2021 in upholding regulatory legitimacy, ensuring social legitimacy through transparency, and ensuring a solid legal and financial foundation for the Surumana Village mangrove ecosystem to be managed protectively and sustainably.